2003
DOI: 10.1523/jneurosci.23-03-00994.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Gray Matter Loss in Alzheimer's Disease

Abstract: We detected and mapped a dynamically spreading wave of gray matter loss in the brains of patients with Alzheimer's disease (AD). The loss pattern was visualized in four dimensions as it spread over time from temporal and limbic cortices into frontal and occipital brain regions, sparing sensorimotor cortices. The shifting deficits were asymmetric (left hemisphere > right hemisphere) and correlated with progressively declining cognitive status (p < 0.0006). Novel brain mapping methods allowed us to visualize dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

83
760
8
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 1,015 publications
(884 citation statements)
references
References 98 publications
83
760
8
3
Order By: Relevance
“…The cortical pattern-matching technique 70 is an advanced computational anatomy imaging methodology that uses sulcal constraints while elastically deforming each subject's cortical morphology into the group average representation. Cortical surface models, derived from structural MRI data, may be used to display a wide variety of imaging data, such as cortical thickness, gray matter density, functional activation data, or metabolic data from PET scans.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…The cortical pattern-matching technique 70 is an advanced computational anatomy imaging methodology that uses sulcal constraints while elastically deforming each subject's cortical morphology into the group average representation. Cortical surface models, derived from structural MRI data, may be used to display a wide variety of imaging data, such as cortical thickness, gray matter density, functional activation data, or metabolic data from PET scans.…”
Section: Figmentioning
confidence: 99%
“…70 The baseline gray matter density comparison 17 compared the baseline hippocampal radial atrophy of MCI subjects who converted to AD and MCI subjects who remained stable or improved cognitively during the 3 years of clinical follow-up. The top row shows a schematic representation of the hippocampal subfields based on two established sources.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) scans of AD patients reveal the greatest degree of atrophy in the temporal and parietal lobes, with frontal lobe damage delayed until the late stages of the disease [18][19][20]. Likewise, functional MRI studies have shown that the most pronounced differences in blood flow between AD patients and controls occur in the temporal and parietal lobes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Following the pioneering work by Bookstein, Grenander and Bajscy [4], [8], [22], the past several years have seen an explosion in the use of template matching methods in computer vision and medical imaging [3], [14], [24], [25], [30], [33], [36]- [40], [51], [53]- [56]. These methods have enabled the systematic measurement and comparison of anatomical shapes and structures in biomedical imagery leading to better understanding of neurodevelopmental, neuropsychiatric and neurological disorders in recent years [5], [6], [11], [13], [17], [20], [42]- [48], [50], [52], [59]. The mathematical theory of Grenander's deformable template models, when applied to these problems, involves smooth invertible maps (diffeomorphisms), as presented in this context in [55], [56], [14], [41], [36] and [33].…”
Section: Introductionmentioning
confidence: 99%